Pengaruh Media Sosial terhadap Gaya Hidup Mahasiswa FKIK Universitas Jambi - Maulina, Elora; Safitri, Shandrina; Rahma, Marsha Davina; Bagaskara, Muhammad Farrel; Sari, Egi Purnama; Beny Rahim; Jelpa Periantolo (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The objectives of this study are: (1) to determine the influence of social media on Jambi University; (2) to determine the lifestyle of Jambi University students. This type of quantitative research is Kuantitatif descriptive statistical . The research population is Civics Students of Jambi University. This research used observation, questionnaire distribution and interview techniques. The results showed that: (1) there is an influence of social media on students of Jambi University, which makes social media a means to access information, find entertainment, and as a medium for communication; (2) there is an influence on the lifestyle of Jambi University students in using social media depending on the content that is often enjoyed when accessing Instagram. Besides that, students of Jambi University, often use social media as a reference to see the latest trend; (3) there is an influence of social media on the lifestyle of students of Jambi University